2020
DOI: 10.3390/bioengineering7020040
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose-Based Inks for 3D Bioprinting: Key Aspects in Research Development and Challenging Perspectives in Applications—A Mini Review

Abstract: Nanocelluloses have emerged as a catalogue of renewable nanomaterials for bioink formulation in service of 3D bioprinting, thanks to their structural similarity to extracellular matrices and excellent biocompatibility of supporting crucial cellular activities. From a material scientist’s viewpoint, this mini-review presents the key research aspects of the development of the nanocellulose-based bioinks in 3D (bio)printing. The nanomaterial properties of various types of nanocelluloses, including bacterial nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 103 publications
(137 reference statements)
1
68
0
Order By: Relevance
“…Some studies have shown that oxidised nanocellulose materials are susceptible to hydrolysis and hence could be degraded in human body. 289 With regards to its application in electronics, thermal resistance between the nanofiller and substrate in 3D printed construct should be carefully designed to provide an effective thermal conductivity and dissipation of heat.…”
Section: Research Gap and Future Perspectivementioning
confidence: 99%
“…Some studies have shown that oxidised nanocellulose materials are susceptible to hydrolysis and hence could be degraded in human body. 289 With regards to its application in electronics, thermal resistance between the nanofiller and substrate in 3D printed construct should be carefully designed to provide an effective thermal conductivity and dissipation of heat.…”
Section: Research Gap and Future Perspectivementioning
confidence: 99%
“…Similar to FDM, DIW is also a high-efficiency method to deposit multi-material printed parts because it is of low cost and can be simply carried out [ 95 , 96 , 97 , 98 ]. More importantly, DIW exhibits tremendous potential because it is highly suitable for printing a large variety of different functional materials through multiple inkjet heads or nozzles to deposit different materials, including metallic particles [ 99 , 100 , 101 ], ceramic particles [ 102 , 103 , 104 ], extracellular matrices [ 105 , 106 , 107 , 108 ], hydrogels, and elastomers and epoxy thermosets [ 109 , 110 , 111 112 ]. As a result, DIW with multiple nozzles has become a favored candidate for multi-material 3D printing.…”
Section: Systematic Review Of Current Researchmentioning
confidence: 99%
“…Yet, due to the novelty of this niche market, no bioprinter reviews that we could find focus on the latest commercially available low-cost systems. Specifically, the previously published reviews either give an overview of the entire bioprinting field (with a focus on the evolution of the printing technologies), 913 review bio-inks, 1427 or discuss specific applications (e.g., cardiovascular tissue models, 14,2835 bone tissue models, 3648 cartilage tissue models, 42,47,4952 nerve tissue models, 5361 skin tissue models, 48,6266 and in vivo bioprinting 67…”
Section: Introductionmentioning
confidence: 99%